Consumption trends of pharmaceuticals and psychoactive drugs in Latvia determined by the analysis of wastewater. (1st August 2022) - Tomsone, Laura Elina; Perkons, Ingus; Sukajeva, Veronika; Neilands, Romans; Kokina, Kristina; Bartkevics, Vadims; Pugajeva, Iveta
Highlights: Wastewater-based epidemiology was used for lifestyle and health pattern assessment in Riga, Latvia. Consumption of 57 pharmaceuticals and 3 recreational drugs was estimated. 5-HIAA was used for normalisation of the concentrations of selected drugs. Seasonal and weekly variations during 2021 were investigated. Abstract: Wastewater-based epidemiology (WBE) was applied to evaluate seasonal variations of the consumption of pharmaceuticals (i.e. antibiotics, NSAIDs, antiepileptics, antihypertensives and others), caffeine, alcohol and nicotine in Latvia throughout 2021. In addition, weekly variation of caffeine, nicotine and alcohol consumption was investigated. Pronounced seasonality was observed in the consumption of antibiotics and decongestants, as well as caffeine, nicotine and alcohol. Correlation with COVID-19 statistics was observed in the case of macrolide antibiotics and antiasthmatic salbutamol. Comparison of the estimated consumption values obtained using the WBE approach and the statistics revealed that the majority of compounds data are in good agreement except angiotensin II receptor blocker group antihypertensives where the most overestimated consumption values were observed. Graphical abstract: Image, graphical abstract